Sources for skeletal muscle repair: from satellite cells to reprogramming. Issue 2 (12th January 2013) - Sirabella, Dario; De Angelis, Luciana; Berghella, Libera
Abstract : Skeletal muscle regeneration is the process that ensures tissue repair after damage by injury or in degenerative diseases such as muscular dystrophy. Satellite cells, the adult skeletal muscle progenitor cells, are commonly considered to be the main cell type involved in skeletal muscle regeneration. Their mechanism of action in this process is extensively characterized. However, evidence accumulated in the last decade suggests that other cell types may participate in skeletal muscle regeneration. Although their actual contribution to muscle formation and regeneration is still not clear; if properly manipulated, these cells may become new suitable and powerful sources for cell therapy of skeletal muscle degenerative diseases. Mesoangioblasts, vessel associated stem/progenitor cells with high proliferative, migratory and myogenic potential, are very good candidates for clinical applications and are already in clinical experimentation. In addition, pluripotent stem cells are very promising sources for regeneration of most tissues, including skeletal muscle. Conditions such as muscle cachexia or aging that severely alter homeostasis may be counteracted by transplantation of donor and/or recruitment and activation of resident muscle stem/progenitor cells. Advantages and limitations of different cell therapy approaches will be discussed.